In situ strain tuning of the metal-insulator-transition of Ca2RuO4 in angle-resolved photoemission experiments. Issue 1 (December 2018) - Riccò, S.; Kim, M.; Tamai, A.; McKeown Walker, S.; Bruno, F.; Cucchi, I.; Cappelli, E.; Besnard, C.; Kim, T.; Dudin, P.; Hoesch, M.; Gutmann, M.; et al.
Abstract Pressure plays a key role in the study of quantum materials. Its application in angle resolved photoemission (ARPES) studies, however, has so far been limited. Here, we report the evolution of thek -space electronic structure of bulk Ca2 RuO4, lightly doped with Pr, under uniaxial strain. Using ultrathin plate-like crystals, we achieve uniaxial strain levels up to −4.1%, sufficient to suppress the insulating Mott phase and access the previously unexplored electronic structure of the metallic state at low temperature. ARPES experiments performed while tuning the uniaxial strain reveal that metallicity emerges from a marked redistribution of charge within the Rut 2g shell, accompanied by a sudden collapse of the spectral weight in the lower Hubbard band and the emergence of a well-defined Fermi surface which is devoid of pseudogaps. Our results highlight the profound roles of lattice energetics and of the multiorbital nature of Ca2 RuO4 in this archetypal Mott transition and open new perspectives for spectroscopic measurements. The role of the lattice in the correlated metal-insulator transition of Ca2 RuO4 has led to significant interest but experiments that are at the same time sensitive to crystal and electronic structure are difficult. Riccò et al. successfully combine ARPES measurements with in situ strain tuning across the Mott transition.